The Influence of Indonesian Language Learning toward Literature on Library Used by Class VIII-4 Students of SMP Negeri 1 Pringgasela - Suryanirmala, Neni; Haeri, Zul; Arifin, Baiq Desi (Jurnal Ilmiah Mandala Education (JIME), 2024)
Education is an important element that shapes a person's character or supports the progress of a nation which can influence the success of the young generation of nation builders now or in the future. Formally, education held in schools is often known as teaching, namely the teaching and learning process which involves many factors, including students, teaching, facilities, materials and the environment. This research is field research which uses a quantitative approach. The quantitative research method in this research is a type of research with a regression and correlation approach. Regression is an approach that predicts the influence of other data or an approach that has a functional relationship between variables. Learning Indonesian Language and Literature at SMP Negeri 1 Pringgasela is classified as good or high level. Based on the results, the author can conclude that 59.77% of respondents use the library collection for Indonesian language and literature subjects twice a week. Apart from that, library use by class VIII-4 students at SMP Negeri 1 Pringgasela is classified as good. Based on the results, the author can conclude that 4.27% of respondents used library collections as a source of information to increase knowledge so that students gain insight and obtain materials or materials to increase knowledge.